Phasal Syntax = Cyclic Phonology?. (June 2016) - Cheng, Lisa Lai‐Shen; Downing, Laura J.
Abstract: This paper addresses three central questions in the phonology–syntax interface: What does phonology know about syntax? Does phrasal phonology "know" about syntax directly or indirectly (i.e., mediated by prosodic constituents such as Intonation Phrase)? When does the phonology–syntax interaction take place? Most current phase‐based theories of the interface assume a strict cyclic model of derivation, in which the output of each spell‐out domain directly feeds the phonology. We argue instead for an indirect model in which phonology is mainly conditioned by phase edges and accesses syntax only when the syntactic derivation is complete. We motivate the model mainly with data from Bantu languages that have played a leading role in the development of current theories of the phonology–syntax interface.